Influence of scattered Greek juniper trees on soil properties in semi-arid woodlands in the northwest of Iran - Younes Rostamikia; Mohammad Matinizadeh; Sohrab Mohtaram Anbaran (Journal of Forest Science, 2024)
Scattered Greek juniper (Juniperus excelsa M. Bieb.) trees have ecological values, such as soil protection and soil erosion reduction in the Irano-Turanian region; however, intensive exploitation puts their habitats at risk. Therefore, knowing the soil characteristics of these habitats plays an important role in their management. The aim of this study was to investigate the soil quality of semi-arid woodlands dominated by a pure Juniperus excelsa community. At three sites in the Irano-Turanian region, soil samples were randomly taken from a depth of 0-20 cm in the eastern direction under the crowns of Greek juniper trees and from bare soil. The evaluated physical properties included bulk density (Bd), moisture, sand percentage, silt percentage and clay. Chemical properties included pH, electrical conductivity (EC), organic carbon (SOC), total nitrogen (TN), and nutrient concentrations of bare soil compared to the below-crown soil. Additionally, we investigated basal respiration (BR) and microbial biomass carbon (MBC) to evaluate the influence of Greek juniper trees on soil microbial activity. The bulk density value in samples taken under crowns was significantly lower by 42% compared to bare soil; however, significantly higher soil moisture (+39.8%) was obtained under tree crowns. Although clay and sand content under tree crowns was significantly higher than that of bare soil, sand content under tree crowns was significantly lower than in bare soil. According to our findings, soil pH under tree crowns and in bare soil was 7.13, which increased to 7.67 in bare soil. Soil EC (+15%), SOC (+76%), and TN (+29%) were significantly higher under tree crowns. The concentrations of magnesium and sodium were similar between bare and below-crown soils, but significantly higher phosphorus (+46%), potassium (+41%), calcium (+31.1%), iron (43.3), and zinc (+56.6%) were observed under Greek juniper crowns. Soil microbial activity was higher under tree crowns compared to bare soil, as evidenced by significantly increased BR (+49.1%) and MBC (+43.5%). Our findings indicate that scattered Greek juniper trees can improve soil properties, and their destruction leads to a significant decrease in soil quality. Generally, planting Greek juniper seedlings in degraded areas can help restore the soil quality.